Symbolizm złotego pasa Chrystusa zmartwychwstałego (Ap 1,13) w świetle literatury greckiej - Podeszwa, Paweł Adam (Verbum Vitae, 2021)
The article deals with the symbolic meaning of Jesus’ golden sash (Rev 1:13) in the inaugural vision of Revelation (1:12-20). The source of this chromatic symbolism is first found in The Old Testament, in the light of which gold color points at Jesus as God, King, and High Priest. In the proposed reflection, the author looks for the possible source (of inspiration) in ancient Greek literature, especially in mythological depictions of divinities: Zeus, Poseidon, Artemis, Apollo, and Circe. The analysis of chosen fragments, cited from Homer’s Iliad and Odyssey and Challimachus’ Hymns, enable us to ascertain that gold is the dominant color and that many elements of garment, inventory, and equipment used by Greek divinities are made from this valuable material. It becomes clear that gold or gold ore is naturally associated with diety and is the “color of gods.” The author of Revelation could use images and motives borrowed from Greek imagery and mythology, treating them as literary material which symbolically expresses the truth about Jesus’ transcendence.